2017
DOI: 10.1080/10717544.2016.1233592
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous monitoring of the drug release and antitumor effect of a novel drug delivery system-MWCNTs/DOX/TC

Abstract: Monitoring drug release and therapeutic efficacy is crucial for developing drug delivery systems. Our preliminary study demonstrated that, as compared with pristine multiwalled carbon nanotubes (MWCNTs), transactivator of transcription (TAT)-chitosan functionalized MWCNTs (MWCNTs-TC) were a more promising candidate for drug delivery in cancer therapy. In the present study, a MWCNTs/TC-based drug delivery system was developed for an anticancer drug, doxorubicin (DOX). The drug loading and in vitro release profi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 40 publications
1
20
0
Order By: Relevance
“…BCNDs play a protective role on the heart, kidney, and other tissues. This conclusion is similar to that of other nanotube drug delivery systems (Dong et al, 2017;Zhang et al, 2019c). In addition to its therapeutic effect on tumors, drug-loaded nanodrops also show a protective trend for other organs.…”
Section: Groupsupporting
confidence: 87%
“…BCNDs play a protective role on the heart, kidney, and other tissues. This conclusion is similar to that of other nanotube drug delivery systems (Dong et al, 2017;Zhang et al, 2019c). In addition to its therapeutic effect on tumors, drug-loaded nanodrops also show a protective trend for other organs.…”
Section: Groupsupporting
confidence: 87%
“… 2010 ; Dong et al. 2017 ). To overcome these obstacles, drug delivery system (DDS) has been thoroughly investigated and extensively used to develop nano-scale formulations for improving the therapeutic efficacy and reducing the side-effects, especially the stimuli-responsive biomaterials-based DDSs (Gong et al.…”
Section: Introductionmentioning
confidence: 99%
“…For example, DOX which can interact with DNA by intercalation and inhibition of macromolecular biosynthesis is one of the most effective drugs for a wide range of cancers including breast cancer, bladder cancer, lymphoma, and acute lymphocytic leukemia (Soma et al 2000;Sharma 2017;Sun et al 2019;Zhou et al 2020). Even though DOX was approved for medical use in the United States 45 years ago (Agarwal et al 2011), the side-effects severely limit the wide use in clinic, such as hair loss, bone marrow suppression, vomiting, rash, and inflammation of the mouth, especially the dilated cardiomyopathy which can lead to congestive heart failure (Singal and Iliskovic 1998;Chatterjee et al 2010;Dong et al 2017). To overcome these obstacles, drug delivery system (DDS) has been thoroughly investigated and extensively used to develop nano-scale formulations for improving the therapeutic efficacy and reducing the sideeffects, especially the stimuli-responsive biomaterials-based DDSs (Gong et al 2012;Mura et al 2013;Yin et al 2013;Li et al 2014;Sun et al 2014;Masood 2016;Qiao et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Dong et al explored the potential of MWCNTs-transactivator of transcription-chitosan (TC) as carriers of DOX against BEL-7402 cells in vitro, which demonstrated that this drug delivery system had good treatment efficacy on cancer and revealed its application potential for cancer therapy. 101 It is well known that CNTs play an important role in gene therapy. Huzil et al compared metallic SWCNTs with semiconducting CNTs on siRNA delivery; the results in murine PAM212 keratinocytes showed that metallic SWCNTs can be transferred into the nucleus, while the transport of semiconducting CNTs was limited since they could only only enter the cytoplasm.…”
Section: Carbon Nanotubesmentioning
confidence: 99%